Toxicity of Polyalthia longijolia against fungal pathogens of rice - S. N. TEWARI, MANASI MISHRA and (Indian Phytopathology, 2002)
Ethanolic extract and essential oil of leaf of Polyalthia longifolia were tested Â against five rice pathogens, viz., Pyricularia oryzae, Rhizoctonia solani, Fusarium moniliforme, Aspergillus niger and Curvularla lunata. Ethanolic extract besides being more effective, possessed broad spectrum fungi toxicity than essential oil.